P174 Defining Crohn's Disease Strictures Using Intestinal Ultrasound Compared to Histopathology. (27th May 2021) - Cooper, J; Danois, K; Koro, K; Wilson, S; Medellin, A; Ma, C; Novak, K; Seow, C; Kaplan, G; Panaccione, R; Lu, C
Abstract: Background: Fibrostenotic Crohn's Disease (CD) is a challenging phenotype often requiring surgical resection. MRE (magnetic resonance enterography) is commonly used to diagnose CD strictures, but is limited by access, cost, and long acquisition time. The CONSTRICT consensus criteria for defining CD strictures is based only on MRE or CT (computed tomography) and includes: increased bowel wall thickness (BWT), narrowed luminal apposition, and pre-stenotic dilation > 3cm. This definition has not been studied using intestinal US (IUS). IUS is a cost-effective, easily repeatable, and well-tolerated tool with similar sensitivity and specificity to MRE in diagnosing and monitoring CD. In patients with a confirmed CD stricture on ileal resection (gold standard for diagnosis), we aim to assess the applicability of CONSTRICT criteria in diagnosing strictures with IUS. Methods: In this pilot study, thirty CD patients who underwent small bowel resection from 2015–2019 with IUS (fasting, no oral contrast) within 6 months prior to surgery (excluding fistulizing disease) were randomly identified for chart review Stricture was confirmed on resected ileum as microscopic presence of fibrosis, muscle hypertrophy, inflammation, and macroscopic localized luminal narrowing with decreased circumference on pathology. Student's t-tests, sensitivities and specificities were calculated for IUS in detecting strictures. Results: 20 out of 30 patients had fibrostenosis on pathology and IUS. Only 40% (8/20) met CONSTRICT criteria for stricture diagnosis on IUS, despite having a stricture on pathology. All patients had elevated BWT and luminal narrowing, but 60% (12/20) of patients did not have prestenotic dilation > 3cm. Mean dilation was 2.9 cm (SD 1.38) and was significantly different from the mean stricture diameter of 1.3cm (SD 0.59 cm, p=0.0001, 95% CI: 0.9–2.2). Mean BWT was 8.7 mm (SD: 2.5, range 5–15), and mean luminal apposition was 2.3 mm (SD 1.2, range 0.2–5.8mm). IUS has a sensitivity of 95.2% (CI: 76.2 - 99.9%) and specificity of 66.7% (29.9 - 92.5%) in detecting strictures, when compared to the gold standard. Conclusion: Diagnosis of fibrostenotic CD with CONSTRICT criteria using CT/MR may not be applicable to IUS. Only 40% of patients met criteria despite histologic-confirmed strictures. Unlike MR/CTE, IUS is not routinely performed with oral contrast, and as a result prestenotic dilation may be underestimated. Thus, perhaps additional criteria of stricture diameter < 50% of prestenotic dilation size is more appropriate for IUS. This pilot study provides the initial data to further delineate the definition of strictures on IUS for future validation and will inform both clinical practice and trial design.